Rigoutorum a new genus for Diaphonia bacchusi Rigout and Allard (Coleoptera: Scarabaeidae: Cetoniinae: Schizorhinini), with description of a second species from Western Australia and notes on habitats and behaviours - Hutchinson, Paul M.; Moeseneder, Christian H.; Mitchell, Andrew (Zootaxa, 2022)
Rigoutorum new genus Hutchinson & Moeseneder (Coleoptera: Scarabaeidae: Cetoniinae: Schizorhinini: Schizorhinina) is created for Diaphonia bacchusi Rigout & Allard, 1997, resulting in Rigoutorum bacchusi new combination. Rigoutorum jakli Hutchinson & Moeseneder, new species, which has been lumped with R. bacchusi in collections and confirmed as distinct through our molecular work, is described. The males and females of both species are described or redescribed. Rigoutorum is diagnosed and compared with Diaphonia Newman, 1840 and Aurum Hutchinson & Moeseneder, 2019, the most similar genera. Habitat and behavioural observations are given, and a distribution map shows that the two species of this endemic genus occupy different climatic regions in southern Western Australia, Australia.